Robin Cooke, Human Rights and the Pacific Dimension - Kirby, Michael (Victoria University of Wellington Law Review, 2008)
Lord Cooke’s life as lawyer and judge was astonishing in its achievements. The author traces his counter-cultural embrace of notions of human rights both in case decisions and in scholarly articles. He describes Lord Cooke’s approach to judging – a mixture of orthodoxy and radical new ideas. He describes his contribution to the emergence of a distinctive New Zealand jurisprudence, curiously asserted in advance of the termination of Privy Council appeals and before similar "liberation" in Australia. The author concludes with a reminder of Lord Cooke’s prediction of a "common law of the world". He suggests that building an effective regional human rights mechanism for the Pacific would be a timely and practical contribution to that ideal.